A coherent, representative, and bioregional marine reserve network shows consistent change in rocky reef fish assemblages. Issue 4 (6th April 2021) - Knott, N. A.; Williams, J.; Harasti, D.; Malcolm, H. A.; Coleman, M. A.; Kelaher, B. P.; Rees, M. J.; Schultz, A.; Jordan, A.
Abstract: Worldwide, several countries have established coherent, representative, and large‐scale networks of marine reserves to conserve biodiversity. Very few have, however, published systematic assessments of the ecological responses to this network protection, hindering broad understanding of their generality, utility, and efficacy. We present data collected from systematic sampling of rocky reef fish assemblages at sites across a network of 27 no‐take marine reserve areas (NTMR) and 27 partially protected areas (PPA) nested within multiple marine parks (regional networks) across three Australian bioregions spanning >1000 km of coastline (7° latitude) to test the generality of ecological change across this network. We also sampled 18 reference areas (outside of the marine parks) to provide an independent assessment of potential NTMR effects and also to assess whole marine park effects. Baited remote underwater video (BRUV) was used to sample fishes between depths of 20–40 m over austral winters in four years (2010, 2011, 2015, and 2016). Despite substantial bioregional differences in fish assemblages, large and consistent effects of NTMR protection were detected across all bioregions for a key commercially and recreationally harvested species, Chrysophrys auratus (pink snapper). There were substantial increases in relative abundance of C. auratus in NTMR compared with fished zones through time (effect sizes >150%). The wider assemblage of targeted fish (excluding C. auratus ) only showed relatively small effects of protection (~11%) with trends observed for site‐attached wrasses (labrids) and planktivores (e.g., commercially fished Scorpis lineolata ) that are recreationally and commercially harvested. Furthermore, the relative abundance of non‐target or by‐catch species generally did not differ among management zones across the bioregional network. These results highlight how NTMR can be used to assess the ecological effects of fishing and wider environmental management, and can be incorporated into ecosystem‐based management for reef species more generally. Importantly, the provision of robust evidence of the performance and generality of NTMR over large‐spatial scales (e.g., bioregions) provides greater confidence in the expected outcomes from marine reserve networks as a conservation management approach.